2005
DOI: 10.1378/chest.128.4.1951
|View full text |Cite
|
Sign up to set email alerts
|

Readmission to an Intensive Care Unit After Lung Transplantation: Experience of a Single Center

Abstract: Heroin and cocaine use are common among adult asthmatic patients admitted to an inner-city hospital. Both cocaine and heroin are significantly associated with the need for intubation. Based on these findings, it may be prudent to screen adults with asthma presenting to an urban emergency department for cocaine and heroin use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[ 3 4 ] Another Chicago hospital reported both cocaine and heroin use as a risk for intubation in asthma. [ 5 ] There are few if any published data on the linkage between heroin use and asthma exacerbations of lesser severity, not requiring ICU admission.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 4 ] Another Chicago hospital reported both cocaine and heroin use as a risk for intubation in asthma. [ 5 ] There are few if any published data on the linkage between heroin use and asthma exacerbations of lesser severity, not requiring ICU admission.…”
Section: Introductionmentioning
confidence: 99%
“…2005 found that cocaine and heroin abuse increased the rate of intubations and hospital utilization in patients with acute asthma exacerbation. [11]…”
Section: Introductionmentioning
confidence: 99%